Ketersediaan Fasilitas Pendidikan SLTA dan Estimasi Peserta Didik untuk Proyeksi Kebutuhan Ruang Belajar Di Kabupaten Wonosobo Tahun 2029 - Setiawan, Heru; Hardati, Puji; Kurniawan, Edi (Jurnal Sains Geografi, 2025)
The increasing trend in school participation at the SLTA level (SMA/SMK/MA) in Wonosobo Regency has led to a rising demand for educational facilities, particularly classrooms. This study aims to analyze facility availability, project student enrollment, and identify additional classroom needs in 2029. A quantitative-descriptive approach was employed. The analysis shows there are 70 SLTA units with varying service capacities. By 2029, student enrollment is projected to reach 36,448, with distribution patterns following the availability of existing facilities. Classroom demand increases in line with student growth. Currently, there is both a shortage and surplus of 82 classrooms, with shortages mainly found in public SLTA. The additional classroom need by 2029 is estimated at 156 units. To promote equitable access, service coverage, and reduce centralization, new public SLTA are recommended in Garung, Kejajar, and Leksono Districts.